DESKRIPSI KOMPETENSI MANAJERIAL KEPALA SEKOLAH SMA SE KECAMATAN RAMBAH HILIR TAHUN PEMBELAJARAN 2015/2016 - Wati, Mira (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This Study Was aimed to description competention of head master managerial at senior high school in Rambah Hilir subdistrict. This study is descriptive research. This study using satisfied method which population as sample. The sample of this study is head master at senior high shcool in Rambah Hilir subdistrict. The sample of this study is head master at senior high shcool in Rambah Hilir subdistrict. The instrument of this study is questioner of indicator competention head master managerial. Results showed that indicator competention head master managerial an average of 71,70%, which concluded to complete category.